Thermal Evaporation of Thin Films: Review - Ho, Soon Min (IDOSI Publications, 2015)
This work reviews recent articles published on the subject of thermally evaporated thin films. Deposition of binary, ternary and quaternary thin films has been successfully carried out by many researchers by using this technique. The properties of thin films were determined using different analysis methods such as X-ray diffraction, scanning electron microscopy and UV-Visible spectrophotometer.